Phyletic evolution of calcareous nannofossil species Reticulofenestra oamaruensis: An example of microevolution preserved at IODP Site U1553 (Southern Pacific Ocean) - Catelli V.; Persico Davide; Righi D.; Raffi I.; Fioroni C.; Villa Giuliana. (Marine Micropaleontology, 2025)
The IODP Expedition 378 in the Southern Ocean (Campbell Plateau) recovered a Paleogene sedimentary section at Site U1553, cored through multiple holes (A - E) in the late Eocene-early Oligocene interval. Stratigraphic continuity and good preservation of calcareous nannofossils offered the opportunity to study the phyletic origin of Reticulofenestra oamaruensis, the biostratigraphic marker for the Eocene/Oligocene Transition (EOT) in the Southern Ocean (SO). We performed biometric and morphological analyses on R. oamaruensis and the related species Reticulofenestra clatrata, revealing intermediate morphotypes with characters between R. clatrata and R. oamaruensis. These transitional morphotypes, labeled Reticulofenestra transitional form 1 (R. t1) and Reticulofenestra transitional form 2 (R. t2), differ in size from the end members and are distinguished in two size categories: 10–12 μ m and 12–14 increase of R. clatrata(8–10 μ μ m respectively. The intraspecific evolutionary trend shows a gradual size m) that, through intermediate steps represented by R. t1 and R. t2, leads to R. oamaruensis (≥14 μ m). The two morphotypes are included in the species identification of R. oamaruensis and enter the stratigraphic record at successive levels, thus delineating a “lineage zone” useful in SO biostratigraphy. R. clatrata and medium – large R. oamaruensis disappear close to the Eocene/Oligocene Boundary. Based on the morphological homology, the progressively increasing size trend from R. clatrata to R. oamaruensis, their stratigraphic range continuity, and their same geographical distribution, we document a phyletic strain endemic to high southern latitudes, of which R. clatrata would represent the archetype.